2012
DOI: 10.4103/2229-4708.97711
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of losartan, losartan acid and amlodipine in human plasma by LC-MS/MS and its application to a human pharmacokinetic study

Abstract: Introduction:A simple, rapid and sensitive liquid chromatography-tandem mass spectrometric assay method has been developed and fully validated for simultaneous quantification of losartan and its active metabolite, losartan carboxylic acid, and amlodipine in human plasma. Irbesartan was used as an internal standard.Materials and Methods:The analytes were extracted from human plasma samples by solid-phase extraction technique using Oasis HLB cartridges, (Waters Corporation, Mumbai, India). The reconstituted samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 23 publications
1
20
0
1
Order By: Relevance
“…The method was validated according to FDA guidelines and all parameters were in the accepted limits. The method was applied for human plasma for kinetic studies and the results were satisfactory [36]. Amlodipine in human plasma was analysed by Feng teamwork using LC-MS. Necardipine was used as internal standard and both drugs were extracted from plasma using ethyl acetate.…”
Section: 42mentioning
confidence: 99%
“…The method was validated according to FDA guidelines and all parameters were in the accepted limits. The method was applied for human plasma for kinetic studies and the results were satisfactory [36]. Amlodipine in human plasma was analysed by Feng teamwork using LC-MS. Necardipine was used as internal standard and both drugs were extracted from plasma using ethyl acetate.…”
Section: 42mentioning
confidence: 99%
“…Karra et al 24 have reported a sensitive method for the simultaneous determination of LOS, EXP-3174, and amlodipine in human plasma. Moreover, the method was used for the pharmacokinetic analysis of only LOS and EXP-3174 in six healthy subjects.…”
Section: Methods Developmentmentioning
confidence: 99%
“…Capillary electrophoresis methods were also used for the analysis of AML in its formulations and biological fluids [15,16]. AML was also determined using liquid chromatography mass spectrometry (LC-MS) [17,18]. 1, 2-naphthoquinone-4-sulphonate (NQS) has been used as a chromogenic reagent for the colorimetric determination of many pharmaceutical amines [19][20][21].…”
Section: Introductionmentioning
confidence: 99%